2004
DOI: 10.5194/angeo-22-3607-2004
|View full text |Cite
|
Sign up to set email alerts
|

Statistical study of high-latitude plasma flow during magnetospheric substorms

Abstract: Abstract.We have utilised the near-global imaging capabilities of the Northern Hemisphere SuperDARN radars, to perform a statistical superposed epoch analysis of high-latitude plasma flows during magnetospheric substorms. The study involved 67 substorms, identified using the IMAGE FUV space-borne auroral imager. A substorm co-ordinate system was developed, centred on the magnetic local time and magnetic latitude of substorm onset determined from the auroral images. The plasma flow vectors from all 67 intervals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
73
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(82 citation statements)
references
References 38 publications
9
73
0
Order By: Relevance
“…Indeed, the fact that these flows clearly cross the open-closed field line boundary implies reconnection driven flow. The development of these flows over the course of the expansion phase, rather than an instantaneous appearance at the time of substorm onset, is corroborated by other recent studies such as those of Jayachandran et al (2003) and Provan et al (2004) which also show a large-scale reaction in the flows over the ∼10-20 mins following substorm onset. What is clear from this study, however, is the addition to these flows of other large-scale flow features, which have previously only been discussed individually.…”
Section: The Large-scale Picturesupporting
confidence: 71%
See 1 more Smart Citation
“…Indeed, the fact that these flows clearly cross the open-closed field line boundary implies reconnection driven flow. The development of these flows over the course of the expansion phase, rather than an instantaneous appearance at the time of substorm onset, is corroborated by other recent studies such as those of Jayachandran et al (2003) and Provan et al (2004) which also show a large-scale reaction in the flows over the ∼10-20 mins following substorm onset. What is clear from this study, however, is the addition to these flows of other large-scale flow features, which have previously only been discussed individually.…”
Section: The Large-scale Picturesupporting
confidence: 71%
“…Grocott et al (2000Grocott et al ( , 2002 presented analyses of Super Dual Auroral Radar Network (SuperDARN) flow data obtained during isolated substorms, and have found evidence for the excitation of twin-vortex flow cells centred in the nightside ionosphere, which enhance the transpolar voltage by ∼40 kV compared with pre-onset values. Following this work, Provan et al (2004) conducted a statistical study of substorm flows and found them to become enhanced across the polar cap and in the low-latitude return flow region. They also found a systematic increase in the transpolar voltage from ∼40 kV 2 min before onset to ∼75 kV 12 min after, and attributed this to the removal of open flux from the polar cap by nightside reconnection.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies using SuperDARN have produced mixed results, however, by providing evidence for both the excitation (e.g. Grocott et al, 2006;Provan et al, 2004) and reduction (e.g. Lyons et al, 2001;Bristow and Jensen, 2007) of the flows following substorm onset.…”
Section: Introductionmentioning
confidence: 99%
“…The two currently available techniques of direct CPCP measurements, i.e., via satellite ion drift data (Hairston et al, 1998) and ground-based radars Grocott et al, 2002;Provan et al, 2004), are both incomplete. This is due to the limited temporal resolution of the satellite measurements, on one hand, and the missing spatial coverage at high latitudes of the present radars, on the other.…”
Section: Introductionmentioning
confidence: 99%
“…The relative contributions to the cross-polar cap potential (CPCP) from the dayside (CPCP/day) and nightside (CPCP/night) sources during intervals of substorm activity have been studied in recent years, applying different observational techniques (Bristow et al, 2004;Lockwood et al, 2009;Kullen et al, 2010;Gordeev et al, 2011;Andalsvik et al, 2011Andalsvik et al, , 2012. Fox et al (1999), Grocott et al (2002) and Provan et al (2004) estimated the convection response to isolated substorms by continuous observations, applying a ground-based radar technique. Grocott et al (2010) studied the convection responses in the dayside and nightside sectors of the polar cap to substorms occurring during intervals of positive and negative interplanetary magnetic field (IMF) B y polarity, applying a superposed epoch analysis.…”
Section: Introductionmentioning
confidence: 99%